Predicting pro-environmental behavior among generation Z in Indonesia: the role of family norms and exposure to social media information - Suminar, Jenny Ratna; Hafiar, Hanny; Amin, Kholidil; Prastowo, Ari Agung (Frontiers in Communication, 2024)
Amidst the pressing concerns of sustainability, it is of utmost importance to prioritize the adoption of reusable bottles to combat plastic waste and encourage pro-environmental behavior (PEB). Moreover, social norms, particularly those within the family, are believed to have the potential to foster the development of PEB. The study investigates how injunctive and descriptive norms influence individuals’ intentions and behaviors regarding pro-environmental behavior (PEB). Additionally, the researchers analyze the communication aspect to evaluate its significance in promoting PEB. The research entailed conducting a cross-sectional survey with 670 respondents in Indonesia who belong to the Generation Z demographic, specifically aged between 18 and 25 years old. The study results indicate that descriptive and injunctive norms are influential factors in determining individuals’ intention to engage in PEB. Besides, the researchers discovered that the intention to engage in PEB is an intermediary in the correlation between descriptive and injunctive norms and PEB behaviors. Another notable finding is that the social media platform Instagram can moderate the influence of intention on PEB behaviors. The study also delves into the theoretical and practical contributions of these findings.